Thermo-hydraulic finite element modelling of district heating network by the uncoupled approach - Gabrielaitienė, Irena; Kačianauskas, Rimantas; Sunden, Bengt (Journal of Civil Engineering and Management, 2003)
The modelling of uncoupled fluid flow and heat transfer problems of a district heating network using the finite element method (FEM) is presented. Since the standard thermo-hydraulic pipe elements cannot be directly used for modelling insulation, the main attention was paid to discretisation of multilayered structure of pipes and surrounding by one-dimensional thermal elements. In addition, validity of the finite element method was verified numerically by solving fluid flow and heat transfer problems in district heating pipelines. Verification analysis involves standard single pipe problems and simulation of fragment of district heating in Vilnius. Pressure and temperature results obtained by finite element method are compared with those by other approaches.First Published Online: 26 Jul 2012